Challenges in implementing new nursing qualifications (Regulation 174) in South African public nursing colleges: Principal perspectives - Poto-Rapudi, Magdeline N.; Masango, Thembekile E.; Mbombi, Masenyani O. (Curationis (Pretoria), 2025)
Background The criticism levelled against the legacy nursing programmes has transformed the health education and training system and the preparation of nursing students to meet society’s needs. The prevailing practice in nursing education (NE) change is orientated towards increasing professionalisation, which necessitates expanding nursing programmes to provide universal health coverage. The South African Nursing Council (SANC) has mandated NE institutions to curriculate and institute the new qualifications in nursing. Objectives This article explores the challenges attendant to the implementation of the new qualifications in nursing at selected public nursing colleges (PNCs) in North-West, Gauteng, Limpopo and Free State provinces. Method A qualitative research design approach was adopted, with semi-structured interviews conducted with 13 purposively sampled participants that were transcribed verbatim. Tesch’s eight-step data analysis method was utilised for the development of the study findings framework. Results The findings revealed challenges such as lack of essential human and infrastructural resources, infrastructural and material limitations, logistical and service constraints and mixed perceptions on the support system available to PNCs ahead of implementing the new qualifications in nursing. Conclusion The perspectives of the principals’ show various challenges that can be categorised into human, institutional, and structural factors. These challenges suggest a need to strengthen the academic support and collaboration between internal and external stakeholders of NE institutions for effectively implementing the new programmes in nursing. Contribution The study findings create awareness for the SANC, Council on Higher Education and Department of Health about the progress of the new nursing programme implementation.